FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU KONSUMEN (MAHASISWA) JURUSAN PIPS DALAM MEMILIH KONSENTRASI IPS TERPADU - Pusposari, Luthfiya Fathi (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2016)
Social Studies Education (PIPS) is one of the Department in FITK UIN Maulana Malik Ibrahim Malang. Based curriculum of PIPS in 2010 is divided two of concentration. First concentration is Economic Education and the second concentration is Integrated Sosial Studies Education. Integrated Sosial Studies Education have been choiced more than 60% of students. This study aims to explain the factors that influence customers (student) behavior in choosing a concentration Integrated Sosial Studies Education. Data obtained from the questionnaire and then analyzed using quantitative descriptive method. The results showed that the main factor influencing consumer behavior in choosing Integrated Sosial Studies Education is Personal factor (74.70%), second factors is Psychologi factor (68.27%), Cultural Factors 50.60% and the last factor is social factor (39.76%).Keywords: Customers (Student) Behaviour, PIPS and Consentration